The Effects of Standard and Low Molecular Weight Heparin on Bone Nodule Formation In Vitro - Bhandari, Mohit; Hirsh, Jack; Weitz, Jeffrey I.; Young, Edward; Venner, Thomas J.; Shaughnessy, Stephen G. (Thrombosis and Haemostasis, 1998)
Previously, we demonstrated in a rat model of heparin-induced osteoporosis that low molecular weight heparin (LMWH) produces less bone loss than unfractionated heparin, and that only heparin increases osteoclast number and activity. In contrast, both heparin and LMWH were found to decrease osteoblast function to a similar extent, possibly because at the doses tested both agents produced maximal inhibition. To examine the relative effects of heparin and LMWH on osteoblast function more closely we used an in vitro bone nodule assay, together with measurements of alkaline phosphatase (ALP) activity. Both agents inhibited bone nodule formation and ALP activity in a concentration-dependent manner, but 6 to 8-fold higher concentrations of LMWH were required to achieve equivalent effects. The effect of heparin on osteoblast function was both chain-length and negative charge-dependent because the ability of defined heparin fragments to inhibit nodule formation correlated with their molecular weight (r = 0.98), and N-desulfated heparin was less inhibitory than heparin. In contrast, the effect of heparin on osteoblast function was pentasaccharide-independent because heparin with low affinity for antithrombin had similar activity to heparin with high antithrombin activity. These findings help to explain mounting clinical evidence that the risk of osteoporosis is lower with LMWH than with heparin.